Peningkatan Literasi Awal melalui Kegiatan Pengenalan Lingkungan Sekolah di Sekolah Alam Jingga Bekasi Utara - Sarah, Siti; Kurniawaty , Lia; Rizawati, Rizawati (Neolectura, 2025)
This research aims to examine the improvement of early literacy skills through environmental introduction activities at Sekolah Alam Jingga, Bekasi Utara. The background of this study is based on the importance of literacy as a fundamental skill for early childhood, serving as the foundation for cognitive, language, and social development. However, preliminary observations indicated that children’s early literacy skills were still varied, literacy activities were often perceived as monotonous, and the use of the school environment as a learning resource had not been fully optimized. The research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, which consists of planning, action, observation, and reflection stages. The study was conducted in two cycles with first-grade students at Sekolah Alam Jingga as the research subjects. Data collection instruments included observation sheets, field notes, and documentation, focusing on indicators of early literacy development such as vocabulary mastery, pre-writing skills, and symbol recognition. The findings revealed that environmental introduction activities significantly improved students’ early literacy skills. This was evident from the increased active participation, curiosity, enthusiasm, and the ability to recognize symbols, letters, and simple words through direct experiences. Learning based on environmental exploration made the process more contextual, meaningful, and enjoyable. Therefore, it can be concluded that integrating environmental introduction activities with literacy learning is an effective strategy to enhance early literacy development in young learners.